IOT UNTUK EFISIENSI PETERNAKAN UNGGAS SKALA RUMAHAN DALAM PROGRAM MANDIRI PANGAN - Ahdiansyah, M. Hafidz; Febiharsa, Dhega; Abdillah, Fuad (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
The home-scale poultry farming sector in rural areas still faces challenges due to manual management that causes instability in the cage environment, waste of feed, and high poultry mortality rates. This condition hinders productivity and is contrary to the vision of the Food Independence Program which encourages village-based food sovereignty. This service activity aims to increase the efficiency and productivity of home-scale poultry farming through the implementation of an Internet of Things (IoT)-based automation system in Mlilir Village, Grobogan Regency. The participatory action research approach is applied through six stages: preparation, socialization, installation of IoT prototypes, technical training, intensive mentoring, and monitoring and evaluation during the trial period. The developed IoT system consists of temperature, humidity, and light sensors, feed and drinking water automation mechanisms, as well as a mobile interface based on ESP32 and Bardi Smart devices. The implementation has succeeded in stabilizing the cage environment, saving feed by up to 12%, reducing poultry mortality by 15%, and increasing the independence of farmers in operating technology. This activity proves that IoT-based appropriate technology can be an effective solution for the modernization of micro farms. The main contribution of the activity is the integration of digital technology with the national policy of Mandiri Pangan, as well as strengthening the digital literacy-based empowerment model at the village level. ABSTRAKSektor peternakan unggas skala rumahan di pedesaan masih menghadapi tantangan akibat pengelolaan manual yang menyebabkan ketidakstabilan lingkungan kandang, pemborosan pakan, dan tingginya angka kematian unggas. Kondisi ini menghambat produktivitas dan bertentangan dengan visi Program Mandiri Pangan yang mendorong kedaulatan pangan berbasis desa. Kegiatan pengabdian ini bertujuan untuk meningkatkan efisiensi dan produktivitas peternakan unggas skala rumahan melalui implementasi sistem otomasi berbasis Internet of Things (IoT) di Desa Mlilir, Kabupaten Grobogan. Pendekatan participatory action research diterapkan melalui enam tahap: persiapan, sosialisasi, instalasi prototipe IoT, pelatihan teknis, pendampingan intensif, serta monitoring dan evaluasi selama periode uji coba. Sistem IoT yang dikembangkan terdiri atas sensor suhu, kelembaban, dan cahaya, mekanisme otomatisasi pakan dan air minum, serta antarmuka mobile berbasis ESP32 dan perangkat Bardi Smart. Implementasi berhasil menstabilkan lingkungan kandang, menghemat pakan hingga 12%, menurunkan angka kematian unggas sebesar 15%, dan meningkatkan kemandirian peternak dalam mengoperasikan teknologi. Kegiatan ini membuktikan bahwa teknologi tepat guna berbasis IoT dapat menjadi solusi efektif untuk modernisasi peternakan mikro. Kontribusi utama kegiatan adalah integrasi teknologi digital dengan kebijakan nasional Mandiri Pangan, sekaligus memperkuat model pemberdayaan berbasis literasi digital di tingkat desa.